Glacial microbiota are hydrologically connected and temporally variable - Cameron, Karen A; Müller, Oliver; Stibal, Marek; Edwards, Arwyn; Jacobsen, Carsten Suhr (Environmental microbiology, 2020)
Glaciers are melting rapidly. The concurrent export of microbial assemblages alongside glacial meltwater is expected to impact the ecology of adjoining ecosystems. Currently, the source of exported assemblages is poorly understood, yet this information may be critical for understanding how current and future glacial melt seasons may influence downstream environments. We report on the connectivity and temporal variability of microbiota sampled from supraglacial, subglacial and periglacial habitats and water bodies within a glacial catchment. Sampled assemblages showed evidence of being biologically connected through hydrological flowpaths, leading to a meltwater system that accumulates prokaryotic biota as it travels downstream. Temporal changes in the connected assemblages were similarly observed. Snow assemblages changed markedly throughout the sample period, likely reflecting changes in the surrounding environment. Changes in supraglacial meltwater assemblages reflected the transition of the glacial surface from snow-covered to bare-ice. Marked snowmelt across the surrounding periglacial environment resulted in the flushing of soil assemblages into the riverine system. In contrast, surface ice within the ablation zone and subglacial meltwaters remained relatively stable throughout the sample period. Our results are indicative that changes in snow and ice melt across glacial environments will influence the abundance and diversity of microbial assemblages transported downstream.
Keywords: mikrobiota; sníh; globální oteplování; Global Warming; Hydrology; Snow; hydrologie; Water Microbiology; Soil; mikrobiologie vody; ledový příkrov; Microbiota; půda; Ice Cover